Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/jacs.5b06982
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Exfoliation of Ultrathin Two-Dimensional Ternary Chalcogenide Nanosheets for Highly Sensitive and Selective Fluorescence DNA Sensors

Abstract: High-yield preparation of ultrathin two-dimensional (2D) nanosheets is of great importance for the further exploration of their unique properties and promising applications. Herein, for the first time, the high-yield and scalable production of ultrathin 2D ternary chalcogenide nanosheets, including Ta2NiS5 and Ta2NiSe5, in solution is achieved by exfoliating their layered microflakes. The size of resulting Ta2NiS5 and Ta2NiS5 nanosheets ranges from tens of nanometers to few micrometers. Importantly, the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(166 citation statements)
references
References 52 publications
(125 reference statements)
2
163
0
1
Order By: Relevance
“…287 Furthermore, single TMDC nanosheets exhibit different affinities for single and double-strand DNAs and efficiently quench the fluorescence of organic molecules, making them promising platforms for sensing of DNA and biomolecules. [288][289][290] Biomedical applications of TMDC nanosheets are described in details in recent reviews. 25,291 The large surface area of TMDC nanosheets render them particularly attractive for diverse energy related applications.…”
Section: Copyright (2014)mentioning
confidence: 99%
“…287 Furthermore, single TMDC nanosheets exhibit different affinities for single and double-strand DNAs and efficiently quench the fluorescence of organic molecules, making them promising platforms for sensing of DNA and biomolecules. [288][289][290] Biomedical applications of TMDC nanosheets are described in details in recent reviews. 25,291 The large surface area of TMDC nanosheets render them particularly attractive for diverse energy related applications.…”
Section: Copyright (2014)mentioning
confidence: 99%
“…Due to the fascinating physicochemical and electronic properties arising from the small dimensions and quantum confinement effects (QCE) [1][2][3], ultrathin nanosheets have been the focus of substantial research in the light of fundamental studies and their broad applications in various fields, including optoelectronic devices [4], energy conversion and storage [5], sensors [6][7][8][9], biomedicine [10], and catalysis [11][12][13][14][15]. In particular, polymeric graphitic carbon nitride nanosheets (GCNNs), an n-type semiconductor, have been receiving considerable attention due to their many intriguing advantages such as the fact that they contain no metal, and nontoxicity, easy availability, sensitive photo-response, excellent chemical and thermal stability, and unique electronic structures [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Besides the morphology of LDH material, the species and quantity of transition metal cations have significant impacts on their catalytic activity. It has been found that incorporate another metal element into FeNi LDH, the most active oxygen evolution reaction (OER) catalyst, can promote the electrocatalytic property on OER.…”
mentioning
confidence: 99%